PENGARUH INDEKS PEMBANGUNAN MANUSIA DAN PDRB SEKTOR PERTANIAN TERHADAP KEMISKINAN DI KALIMANTAN TIMUR - Saripah Nurfilah, Mariyah (LPPM University 17 Agustus 1945 Samarinda, 2022)
The Human Development Index (HDI) is an indicator used to show the population's access to development outcomes and the development ranking of a region. The basic dimensions of HDI with the new method consist of a long and healthy life, knowledge, and a decent standard of living. The objectives of the study were to describe the HDI achievement, employment in the agricultural sector and its contribution to GRDP, and to analyze the effect of the HDI and GRDP of Agriculture on poverty in East Kalimantan. This study uses descriptive analysis and multiple linear regression analysis with variables Mean Length of School, Expenditure per capita (EXP), and Gross Regional Domestic Product of the agricultural sector (GDP). The data used are time series data for the period 2011-2020. The results showed an increase in HDI by 4.22, an increase in GRDP of 28.48 billion, and the percentage of poor people by an average during the 2011-2020 period of 6.25%. The variables of average length of schooling, per capita expenditure, and GRDP in the agricultural sector have a significant effect on the 5% level of poverty, while the variables of school year expectancy and life expectancy have no significant effect on poverty. RLS has a significant effect on increasing poverty, and EXP and GRDP in the agricultural sector have a significant effect on reducing poverty. The implication of the research is to increase the human development index by increasing the quality and quantity of providing education guarantees, social welfare guarantees to the community, as well as increasing income and creating job opportunities.